Coral reef and associated habitat mapping using ALOS satellite imagery - Mustapha, M.A.; Lihan, T.; Khalid, L.I. (Universiti Kebangsaan Malaysia, 2014)
Coral reefs are rich in biodiversity and ecosystem services. However increase in degradation are still occurring at an alarming rate. In management of this ecosystem, determination of its spatial distribution is of importance. Satellite imageries can be used to map distribution extent using spectral characteristics which is a fundamental parameter in mapping. The aims of this study were to determine the spectral characteristics of corals and associated habitats and to map its spatial distribution using 2009 ALOS advanced visible and near infrared radiometer type 2 (AVNIR-2) satellite imagery. Results indicated that coral and habitats surrounding the area display variation in the spectral characteristics magnitude but displays similar spectral curve. Spectral characteristics from the corals and surrounding habitats were determined by presence of benthic microalgae and calcium carbonate. Maximum likelihood classification on the image produced five main classes. Spatial distribution of coral and associated habitats indicated five main zones which are sandy shore zone, sandy intertidal zone, seagrass zone, coral/submerged sandy zone and rocky zone. Distribution of live corals indicated coverage of 0.54 km2, sea grass (0.94 km2), sandy bottom (1.31 km2) and rocky shores (0.19 km2). The results of this study indicated that ALOS satellite data was able to determine variation in spectral characteristics of coral reefs and other habitats thus is capable of mapping the ecosystems spatial distribution.